Acute Tubulointerstitial Nephritis due to Phenytoin: Case Report - Bresolin, Nilzete Liberato; Junior, Pedro Docusse; Shiozawa, Maria Beatriz Cacese; Moreira, Marina Ratier de Brito; Silveira, Natalia Galbiatti (Journal of Clinical Nephrology, 2017)
Introduction: Acute tubulointerstitial nephritis (ATIN) is an acute kidney injury (AKI) resulting from damage to the tubulointerstitial tissue due to infection, trauma, or use of medication. It is clinically non-specific. Case: A teenager with multiple trauma, hospitalised after lowering of level of conscience, and convulsion fits. While in the emergency ward, he received: midazolam, fentanyl and phenytoin. The cranial and abdominal CT scans were normal. He was stable with no signs of shock, trauma or infection; he developed oliguria and serum creatinine (Scr) 1.7mg/dL), 12 hours after the admission. After 36 hours, Scr levels were at 3.4mg/dL and urea at 55mg/dL. He had AKI according to pRIFLE (66.2% reduction in clearance). After other causes of AKI had been ruled out, the possibility of ATIN was raised; the phenytoin was suspended and pulse therapy, with methylprednisolone, was promptly initiated. After the first pulse, there was already a decline in the creatinine and urea readings; 48 hours later: Scr at 2.2mg/dL and urea at 86mg/dL. Thirty days after being discharged from hospital, the patient was in good health and had full restoration of kidney function. Discussion: The singularity of this report relies on the rarity of ATIN secondary to the use of phenytoin and also in the importance of recognizing this aetiology as being one of the origins of AKI. Conclusion: Early diagnosis allows the reversal of AKI through suppression of treatment with phenytoin and introduction of corticosteroid therapy, when necessary.